The Impact of COVID-19 on Clothing Sales - Mateusz KOWALSKI (Communications of International Proceedings, 2021)
The clothing industry is an important sector of the global economy, which is estimated to show an annual growth rate of around 5%. However, the coronavirus pandemic has brought a marked slowdown in the projected value growth of the sector as a whole, becoming a serious challenge for companies operating in the clothing industry. The aim of the paper was to assess the impact that the coronavirus pandemic has had on the functioning of the clothing industry and the change in purchasing trends for clothing products in 2020. The analysis used data from annual reports of selected clothing brands published in 2020, as well as information from reports and analyzes of international non-governmental and consulting organizations about the functioning of the clothing industry during the coronavirus pandemic. The analysis showed that in 2020, the clothing sector recorded the biggest drops in sales levels since the last crisis. With most stores having to close, major clothing companies have reported losses of hundreds of millions of dollars, and millions of workers around the world have lost their jobs as a result of reduced orders and lower levels of clothing production. On the other hand, online commerce has been helpful in surviving the most difficult periods of the pandemic, with its share of overall clothing sales increasing significantly. According to current forecasts, e-commerce channel, e.g. through the use of new technologies such as virtual reality and artificial intelligence, will gain wider recognition in the clothing industry becoming an important direction of its development.
Keywords: Clothing Industry; COVID-19; E-Commerce.